2010
DOI: 10.1016/j.expneurol.2010.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Impaired immune responses following spinal cord injury lead to reduced ability to control viral infection

Abstract: Spinal cord injuries disrupt central autonomic pathways that regulate immune function, and increasing evidence suggests that this may cause deficiencies in immune responses in people with spinal cord injuries. Here we analyze the consequences of spinal cord injury (SCI) on immune responses following experimental viral infection of mice. Female C57BL/6 mice received complete crush injuries at either thoracic level 3 (T3) or 9 (T9), and 1 week post-injury, injured mice and un-injured controls were infected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 38 publications
2
59
0
Order By: Relevance
“…Decreases could reflect the loss of FO B cells observed following SCI, as there would be less initial cells able to respond to antigen encounter. Similarly, although total T cell numbers appear intact following SCI [92], the ability for T cells and specifically T follicular helper cells to interact with B cells and form sustained GCs could be inhibited. In either case, it appears that SCI dysregulation of either the HPA axis or SNS signaling could contribute to failed TD responses.…”
Section: Sci Alters the Magnitude And Quality Of Primary Thymus-depenmentioning
confidence: 99%
“…Decreases could reflect the loss of FO B cells observed following SCI, as there would be less initial cells able to respond to antigen encounter. Similarly, although total T cell numbers appear intact following SCI [92], the ability for T cells and specifically T follicular helper cells to interact with B cells and form sustained GCs could be inhibited. In either case, it appears that SCI dysregulation of either the HPA axis or SNS signaling could contribute to failed TD responses.…”
Section: Sci Alters the Magnitude And Quality Of Primary Thymus-depenmentioning
confidence: 99%
“…There is ample evidence demonstrating that despite an elevated inflammatory state, SCI is associated with a state of immunosuppression and a heightened susceptibility to infection. [6][7][8][9] Suppressed function of natural killer cells, neutrophils, macrophages and lymphocytes have each been documented following SCI. 6,10,11 The loss of motor and sensory function also contribute to this population's greater susceptibility to a number of acute infections, including urinary tract infection (UTI) and pressure ulcers, as well as metabolic disorders associated with a more sedentary lifestyle such as obesity, atherosclerosis and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…9 Damage to the cervical spine would interfere with supraspinal control over preganglionic neurons below the injury, whereas damage at the mid-thoracic region would damage preganglionic sympathetic neurons directly. 7 Level-dependent impairment in B-cell function has been demonstrated in mice subjected to high (T3) versus mid-thoracic (T9) SCI. It was shown that only after high thoracic SCI (causing disruption of autonomic control of the spleen) was splenic norepinephrine elevated and immune function suppressed, 9 whereas mid-thoracic SCI (leaving autonomic control of the spleen intact) has been shown to induce B-cell activation, increase the synthesis of autoantibodies 19 and activate autoreactive T cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In our study, progression from acute to chronic hepatitis B was 50%. Held et al 17 reported that in mice, SCI is associated with the disruption of immune responses due to the interruption of neural pathways that regulate immune effectors functions required to control and eliminate the mouse hepatitis virus infection. These may be the cause of a high rate of progression to chronic HBV infection along with other mechanisms mentioned above.…”
Section: Discussionmentioning
confidence: 99%